Liraglutide effect and action in diabetes-In (LEAD-In): A prospective observational study assessing safety and effectiveness of liraglutide in patients with type 2 diabetes mellitus treated under routine clinical practice conditions in India - Subhash Kumar Wangnoo; Surender Kumar; Arpandev Bhattacharyya; Sudhir Tripathi; Shahid Akhtar; Raman Shetty; Samit Ghosal (Indian Journal of Endocrinology and Metabolism, 2016)
Background: This 26-week, open-label observational study assessed the incidence and type of adverse events (AEs) associated with liraglutide use according to the standard clinical practice settings and the local label in India. Materials and Methods: A total of 1416 adults with type 2 diabetes (T2D) treated with liraglutide in 125 sites across India were included in the study. Participants were newly diagnosed or already receiving antidiabetic medications. Safety and efficacy data were collected at baseline and at approximately weeks 13 and 26. The primary outcome was incidence and type of AEs while using liraglutide, with events classified by Medical Dictionary for Regulatory Activities system organ class and preferred term. The secondary objective was to assess other clinical parameters related to effective T2D management. Results: Twenty AEs, predominately gastrointestinal, were reported in 1.3% of the study population in scheduled visits up to week 26. No serious AEs, including death, were reported. Hypoglycemic episodes were reported in 7.3% of participants at baseline and 0.7% at week 26. No major hypoglycemic events were reported up to week 26 (baseline: 0.4%). Glycated hemoglobin was reduced from baseline (8.8 ± 1.3%) to week 26 by 1.6 ± 1.1% (P < 0.0001); significant improvements in fasting blood glucose, and 2-h postprandial blood glucose (post-breakfast, -lunch, and -dinner) were also observed. Mean body weight decreased by 8.1 ± 6.5 kg from baseline (92.5 ± 14.6 kg; P< 0.0001). Conclusions: From the number of AEs reported, it is suggested that liraglutide was well tolerated in subjects with T2D treated under standard clinical practice conditions in India. Liraglutide was effective, and no new safety concerns were identified.